Effect of constant and cyclic heat stress on growth performance, water intake, and physiological responses in pigs: A meta-analysis - de Oliveira, M. J.K. [UNESP]; Polycarpo, G. V. [UNESP]; Andretta, I.; Melo, A. D.B. [UNESP]; Marçal, D. A. [UNESP]; Létourneau-Montminy, M. P.; Hauschild, L. [UNESP] (Elsevier, 2024)
The purpose of this meta-analysis was to evaluate the influence of heat stress (HS) type on growth, feed intake and efficiency, water intake, tissue deposition, physiological responses, and organ weight of pigs. Data from 7230 pigs were extracted from 112 articles published before January 2022. The screening criteria were as follows, experiments with at least two temperatures (thermoneutral [TN] and HS); pigs getting free access to feed and water; initial body weight (BW) greater than 5 kg; and, studies providing results of average daily feed intake (ADFI) or average daily gain (ADG). Treatments were classified as constant (ConsHS) or cyclic (CyclHS) HS. All responses (Y) to each heat challenge were calculated relative (Δ) to the TN control group, expressed as a percentage of the difference. Overall, HS increased pigs’ respiratory rate by 112%, rectal temperature by 1.63%, and water intake by 60% (P < 0.001). In contrast, HS reduced lipid deposition by 20.6%, and kidneys weight by 10.5% (P < 0.05). In terms of HS-type effects, CyclHS increased pig's skin temperature by 13%, while ConsHS increased by 6.1% (P < 0.001). Under CyclHS, ADFI and ADG were reduced by 15.1% and 15.2%, respectively. The corresponding reductions for pigs under ConsHS were 23.2% and 25.3%, respectively (P < 0.01). Body water deposition and ash deposition of CyclHS pigs were reduced by 28.4% and 27.2%, respectively. The corresponding reductions for ConsHS pigs were 11.1% and 9.6%, respectively (P < 0.05). In comparison to the TN group, only ConsHS pigs had a reduction in protein deposition (9%), and organ weights (heart, 7.4%, liver, 7.3%, and small intestine, 8.3%) (P < 0.05). Tissue deposition calculated as % of ADG was modified in ConsHS pigs that showed an increase in protein and ash deposition by 7.8% and 8.2%, respectively, while lipid deposition was reduced by 8.3% (P < 0.05). Serum albumin levels for ConsHS pigs were reduced by 5.7% (P < 0.001). Regardless of HS type, feed efficiency (FE) was worsened for HS pigs. In addition, maintenance requirements were not altered in CyclHS pigs. However, in ConsHS pigs, 25.7% of the decreased ADG was attributed to changes in maintenance requirements (i.e. not associated with a reduction in feed intake), while 74.3% was associated with changes in FE (i.e. associated with a reduction in feed intake). In conclusion, ConsHS compromised pig performance to a greater extent than CyclHS, which was associated with higher maintenance requirements. Irrespective of the HS type, HS pigs had a disrupted respiratory rate, rectal and skin temperature, and worse FE.
Keywords: Ambient temperature; Organ weight; Performance; Swine; Thermoregulation